The relationship between DEM resolution, accumulation area threshold and drainage network indices - Junming Chen; Guangfa Lin; Zhihai Yang; Hanyue Chen (2010 18th International Conference on Geoinformatics, 2010)
Digital Elevation Model (DEM) is the main and commonly used data in extracting the digital drainage system in a basin. But the result of the extracted drainage networks would have great uncertainty because of introducing accumulation area threshold and the cell size of DEM in the context of scale effect. Therefore, it is of great significance to explore the relationship between the three above factors in detail. The researches reported at present are mainly on that of any two factors qualitatively or quantitatively. It is yet to be answered about how to define the accumulation area threshold and the spatial resolution in a given research area. The paper examined the relationship between the three factors and presented a composite function. Method: the DEM with grid cell size of 2.5(m) in the research area, Xiamen city of Fujian province, P. R. China, was generated using the Digital Line Graphic (DLG) on the scale of 1:10000. The original DEM generated was re-sampled into a series of DEMs with nested grid size as 5(m), 10(m), 20(m), 40(m), 80(m), 160(m) and 320(m) using the Nearest Re-sampling method. Then the D8 algorithm and the Hydrology module in ArcGIS software was employed to extract drainage networks with 7 accumulation area thresholds as 0.9(km 2 ), 2.7(km 2 ), 4.5(km 2 ), 7.2(km 2 ), 9(km 2 ), 13.5(km 2 ) and 18(km 2 ) in all the DEMs above. Then two indices, the length and the density of the drainage networks were calculated and the quantitative composite functions and curve line graph between the indices, the threshold and the DEM resolution were presented as well. Our analysis of the results revealed that: (1) the length and the density of the drainage networks are both obeying the same function format; (2) these two indices are obeying the power function format with threshold, exponential function format with DEM resolution respectively; (3) when thresholds keeps constant, drainage network features are decreased with DEM grid cell size continuously, and vice versa; (4) according to the mathematical analysis of the composite function, the optimum grid cell size is 40(m) and that of accumulation area threshold is 7.2(km 2 ). On the basis of the field work and the integrated analysis of the SPOT5 remote sensing image with spatial resolution of 2.5(m), the drainage network exacted according to the optimum parameters calculated from the composite function containing scale effect reflected the reality of the research area well.